A Method for Evaluating Insecticide Efficacy against Bed Bug, Cimex lectularius, Eggs and First Instars - Campbell, Brittany E. (J Vis Exp, 2017)
Standard toxicity evaluations of insecticides against insect pests are primarily conducted on adult insects. Evaluations are based on a dose-response or concentration-response curve, where mortality increases as the dose or concentration of an insecticide is increased. Standard lethal concentration (LC(50)) and lethal dose (LD(50)) tests that result in 50% mortality of a test population can be challenging for evaluating toxicity of insecticides against non-adult insect life stages, such as eggs and early instar or nymphal stages. However, this information is essential for understanding insecticide efficacy in all bed bug life stages, which affects control and treatment efforts. This protocol uses a standard dipping bioassay modified for bed bug eggs and a contact insecticidal assay for treating nymphal first instars. These assays produce a concentration-response curve to further quantify LC(50) values for insecticide evaluations.